2015
DOI: 10.5433/1679-0359.2015v36n6supl2p4365
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for sperm evaluation using fluorescent probes

Abstract: A variety of laboratory tests were developed to obtain more reliable results of sperm evaluation and increase the accuracy of sperm fertility predictions. These tests detected damage of sperm specific compartments or organelles, which cannot be detected in routine sperm analysis. The use of fluorescent probes and detection using fluorescent microscopy or flow cytometry is an important tool but a more precise and accurate laboratory test is needed. Propidium iodide and 6-carboxyfluorescein diacetate are used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…Acrosome integrity is a vital factor for successful fertilization, which can be detected using LYSO-G dye (Cunha et al, 2015). The present study reported improved AI from post thaw sperm suspended with 8% EG.…”
Section: Discussionsupporting
confidence: 58%
“…Acrosome integrity is a vital factor for successful fertilization, which can be detected using LYSO-G dye (Cunha et al, 2015). The present study reported improved AI from post thaw sperm suspended with 8% EG.…”
Section: Discussionsupporting
confidence: 58%
“…AI is a key indicator of fertility potential. It can be visualized using LYSO-G florescent dye [39]. In the present study, the highest percentage of intact acrosome was found for sperm cryopreserved using 10 µg/mL of AFPIII combined with 8% DMSO.…”
Section: Discussionsupporting
confidence: 50%
“…According to Ravagnan et al (2002), after the rupture of mitochondrial membranes, there is a release of pro-apoptotic factors, which can cause irreparable structural and functional damage to sperm. Although the PI−CMXRos−Hoechst 342 combination was efficient for the analysis of cavies’ sperm, we emphasize that future studies should consider the use of other biomarkers, including those used for the analysis of specific regions of the sperm as the acrosome, chromatin and membranes, as well as those used for evaluating mitochondrial potential and sperm capacitation (Cunha et al , 2015).…”
Section: Discussionmentioning
confidence: 98%